Heterogeneity of Students’ Mathematical Critical Thinking Ability Re-viewed from Education Levels: A Meta-Analysis - Suparman Suparman; Dadang Juandi; Bambang Avip Priatna Martadiputra (PAEDAGOGIA, 2021)
Study of meta-analysis by selecting the random effect model was employed to investigate and examine students’ education level predicted as one of the causative factors of the heterogeneity of mathematical critical thinking ability (MCTA) through problem-based learning (PBL). Search engines such as Google Scholar and Semantic Scholar were used to find thirty journal or proceeding articles published in 2011 – 2021 and indexed by Scopus, Sinta, and Web of Science. The Z and Q Cochrane test were used to analyze the data. The results revealed that education level was one of the significant factors causing the heterogeneity of students’ MCTA through PBL. Therefore, mathematics teachers or lecturers should minimize the gap by improving the learning quality through PBL in education level in which students’ MCTA was still low.